Pengaruh Pemberian Teh Daun Kelor Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi Di Kukusan Beji Depok Tahun 2023 - Aolia Agustin; Risky Kusuma Hartono; Solehudin Solehudin (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Lack of public knowledge regarding traditional medicine, namely the use of Moringa leaves which can lower blood pressure. The aim of this study was to identify the effect of giving kelor leaf tea on reducing blood pressure in hypertension sufferers in Kukusan Beji Depok. Quantitative research method with a pre-experimental approach. The sampling technique used was purposive sampling with a sample size of 15 respondents. Data were collected using a pretest posttest observation sheet given the Moringa leaf tea intervention. The statistical tests used in this research are the Wilcoxon test and the paired sample T-test. Based on the results of the Wilcoxon test on systolic blood pressure, it shows a significance value (p-value = 0.001), the significance value for diastolic blood pressure using the paired sample T-test is (p-value = 0.000). In conclusion, there is an effect of giving Moringa leaf tea on reducing blood pressure in hypertension sufferers in Kukusan Beji Depok in 2023.